The role of the audit committee to increase the influence of audit quality and internal control on earnings management - Sitanggang, Tikkos; Aryati, Titik; Pamungkas, Bambang; Agoes, Sukrisno (Technium Social Sciences Journal, 2022)
This study aims to analyze the effect of audit quality and internal control on earnings management and the role of the audit committee as moderating variable in consumer goods manufacturing companies listed on The Indonesia Stock Exchange for the period 2015 to 2019. The novelty of this study is the measurement of audit quality with a score approach that represents the competence and independence dimensions of audit quality. In addition, the measurement of internal control uses the COSO score.The purposive sampling method resulted in 165 firms-years for analysis. The analytical method used is multiple regression with moderating variables using panel data. Based on the test results, it was found that audit quality has a negative effect on earnings management. Meanwhile, internal control has no effect on earnings management. Furthermore, the results of this study also found that the audit committee was unable to moderate the effect of audit quality and internal control on earnings management.